All around seeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Seed Provision & Agricultural Development By R Tripp, James Currey Publishers, Oxford, 2001. 175 pp. ISBN 0 85255 420 6 GBP 14.95 Euro 24.30